The therapeutic and prognostic value of NOTCH1 and NOTCH3 expression in head and neck squamous cell carcinoma - Karbasian, Mahtab (My University, 2023)
BACKGROUND: Head and neck squamous cell carcinoma (HNSCC) is the most common type of cancer that develops in the upper aerodigestive tract. Throughout the past decades, the mortality rate of HNSCC remains high. As radiotherapy and chemoradiotherapy continue to be the first-line treatments, there is an unmet medical need to investigate novel therapeutic targets or possible biomarker(s) that predict the therapeutic outcome or may assist with an improved prognosis of the disease. Therefore, gaining deeper insights into the molecular pathways involved in this very heterogenous and diverse malignancy is of utmost importance. One major molecular pathway involved in HNSCC initiation and early-stage development is NOTCH signalling which plays an important part in regulating cell survival, proliferation, cell differentiation, and apoptosis. It is well-established that dysregulation of NOTCH signalling has tumorigenesis effects in early-stage cancers. However, only limited information is available concerning the differential role of the 4 NOTCH receptors in HNSCC development and progression, including acquired resistance to therapy. In this study, we assessed the differential effects of two important NOTCH receptors, NOTCH1 and NOTCH3 on the growth and differentiation properties of two NOTCH wildtype HNSCC cell lines. In addition, we investigated the role of these receptors in the response to cisplatin, with or without radiotherapy combination. METHODS: Two HNSCC cell lines (UT-SCC-10 and UT-SCC-24A) were selected for this study and NOTCH1/NOTCH3 protein expression was validated by Western blotting. Next, using siRNAs, each NOTCH receptor's expression was downregulated, and its functional impact on the cells’ growth and morphology was examined in both 2D and 3D organotypic cultures. In addition, the NOTCH1/NOTCH3 knocked-down cells were treated with cisplatin, irradiation, or a combination of both. Finally, the cellular response to these treatments was quantified and evaluated using both phenotypic analysis (live cell imaging) and metabolic cytotoxicity assays. RESULTS: The studied cell lines showed functional and active NOTCH receptors and NOTCH signalling. Our preliminary results from 3D functional assays indicate that NOTCH1 and NOTCH3 have important roles in HNSCC characteristics suggesting that they might act as tumour promoters in the studied cells. More importantly, the obtained results suggest that NOTCH3 could be a potential therapeutic target or a combinatorial treatment strategy with cisplatin-based chemotherapy.
Keywords: Head and neck squamous cell carcinoma, NOTCH signalling pathway